2015
DOI: 10.1155/2015/745647
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Factors in Systemic Lupus Erythematosus: Contribution to Disease Phenotype

Abstract: Genetic factors exert an important role in determining Systemic Lupus Erythematosus (SLE) susceptibility, interplaying with environmental factors. Several genetic studies in various SLE populations have identified numerous susceptibility loci. From a clinical point of view, SLE is characterized by a great heterogeneity in terms of clinical and laboratory manifestations. As widely demonstrated, specific laboratory features are associated with clinical disease subset, with different severity degree. Similarly, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 90 publications
(132 reference statements)
2
62
0
4
Order By: Relevance
“…IFN-a, a product of activated plasmacytoid cells, is thought to exert its SLE effects in part by its ability to potentiate B cell differentiation and Ab secretion in vitro and in vivo to worsen B cell-mediated pathology in SLE mouse models (127). Further support of the role of B cells in SLE come from genetic studies where susceptibility loci in SLE have been described that are involved with B cell-related functions including MHC haplotype Ag presentation and transcription factors involved in B cell Ab production (128)(129)(130). Of particular importance is the genetic association of Aiolos (64) and Ikaros (65), which are essential factors in B cell differentiation and Ab secretion, and in the case of Aiolos, found to be overexpressed in the B cells of SLE patients (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-a, a product of activated plasmacytoid cells, is thought to exert its SLE effects in part by its ability to potentiate B cell differentiation and Ab secretion in vitro and in vivo to worsen B cell-mediated pathology in SLE mouse models (127). Further support of the role of B cells in SLE come from genetic studies where susceptibility loci in SLE have been described that are involved with B cell-related functions including MHC haplotype Ag presentation and transcription factors involved in B cell Ab production (128)(129)(130). Of particular importance is the genetic association of Aiolos (64) and Ikaros (65), which are essential factors in B cell differentiation and Ab secretion, and in the case of Aiolos, found to be overexpressed in the B cells of SLE patients (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ze względu na zwiększoną częstość występowania u rasy czarnej podejrzewa się również udział czynników genetycznych [1,2,3].…”
Section: Wstępunclassified
“…Multiple genes, that are causing SLE, are linked to the function of the immune system and difference in this most likely effect proper controls and targeting of the immune system. Genetic factors along with environmental factors play an important role in the determination of SLE susceptibility [22]. It is suggested that genetic factors play an important role not only in disease susceptibility but also in the development of SLE phenotype [22].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Genetic factors along with environmental factors play an important role in the determination of SLE susceptibility [22]. It is suggested that genetic factors play an important role not only in disease susceptibility but also in the development of SLE phenotype [22]. The genes that can increase SLE susceptibility are the genes included in the interferon pathway, also containing IRF5, IF1H1, and STAT4 [23].…”
Section: Genetic Factorsmentioning
confidence: 99%